What is at stake when Muslims join the ranks? An international comparison of military chaplaincy - Ines Michalowski (Religion, State and Society, 2015)
In this article I analyse the `strategic action field' evolving in five European countries around the inclusion of Muslims into military chaplaincy. I show that cross-national institutional differences in particular with regard to the state–religion relationship have an influence on the accommodation of Muslims in military chaplaincy: countries with a strong focus on equality in their state–religion relationship are the European forerunners in setting up a Muslim military chaplaincy, whereas countries whose state–religion relationship explicitly allows for the differential treatment of religious groups lag behind, in particular if Muslims are among the groups for whom official cooperation with the state is impossible since they have not acquired the requested legal status. At the same time, I show that organisation-specific arguments that push for religious accommodation and equal treatment in the military lead to a convergence of practices across the various European countries. Similar things are `at stake' in the strategic action field that evolves around the inclusion of Muslims into military chaplaincy: the distribution of scarce chaplaincy posts; training and education of chaplains; security and control of religion; attracting new recruits; and assuring social cohesion, as well as being in line with principles of equality and religious liberty. France stands out in this comparison because it reached a high level of Muslim accommodation in military chaplaincy that stands in stark contrast with the limited accommodation of religion reached in state schools. An additional cross-national comparison shows that all European countries in the study differ fundamentally from the USA, where the distribution of chaplaincy posts is organised along a relatively easy market-based system that does not depend on the European institutionalisation of faith-specific military chaplaincies.
Additional information: Eingereichte Fassung (preprint) / Submitted version (preprint)
Keywords: 330; military chaplaincy; religious accommodation; Islam; organisational change; international comparison